An Analysis of Transposition Techniques in Indonesian Subtitle of Knives Out Movie - Ulhaq, Fayza; Yahya, Mohammad; Yuliah, Siti (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2024)
This research focuses on analyzing transposition techniques and the translation quality of the Indonesian subtitle of Knives Out Movie. Subtitles are needed in the entertainment industry, particularly to translate narratives and dialogues, for viewers understanding although the grammatical rules between source and target language are different. This study aims to identify the most dominant type of transposition techniques, and to assess the accuracy and acceptability aspect of the translation quality. This research uses qualitative methods. There are 413 data of Indonesian subtitles applied transposition techniques. The most dominant type is structure shift with 37.31% of the data followed by unit shift with 33.18% of the data, intra-system shift with 22.03% of the data, class shift with 4.12% of the data, and level shift with 3.39% of the data. Shifts occurred because of the grammatical differences between the source language (English) and the target language (Indonesian). For the translation quality assessment, the final score is 2.83, which means the Indonesian subtitles that apply transposition techniques are accurate and acceptable. There are 90% accurate translations and 10% less accurate translations. For acceptability, there are 88% acceptable translations and 12% less acceptable translations. This analysis can enrich research in translation studies and serve as a reference or additional material for the Translation course.